The use of the smartphone as a tool for the search of information in the undergraduate students of Education of a Metropolitan Lima’s university - Figueroa Portilla, Carlos Saussure (2016)
The mobile devices like the tablet and the smartphone, especially this latter, forits portability and easy access to internet, has allowed its use to a massive public,within which are the university students.In this article are shown the results of a quantitative research about how is donethe information search through the educational use of the smartphone by theincoming students of the 2015-I cycle of the education faculty in a MetropolitanLima’s university, who all of them own a smartphone.